Licorice attenuates cisplatin-induced hepatotoxicity by alleviating endoplasmic reticulum stress and apoptosis - Jie Li; Xiujuan Yang; Xiaolong Lian; Baojian Li; Quhuan Ma; Lingling Yang; Guangmiao Gao; Yi Deng; Zhijun Yang (Frontiers in Pharmacology)
Cisplatin (CP), a widely used antineoplastic drug, could induce hepatotoxicity and is also one of the most common reasons for drug-induced liver injury (DILI). Licorice (Chinese name GanCao, GC) is a commonly used herbal drug in traditional Chinese medicine (TCM) that has been shown to treat liver diseases and DILI. CP has been documented to induce apoptosis through the promotion of endoplasmic reticulum (ER) stress. However, the exact role of ER stress in the pathogenesis of CP-induced hepatotoxicity remains unclear. A rat DILI model was constructed through intraperitoneal injection of CP, and the anti-DILI effect of GC was detected by liver coefficients, liver function tests, pathological staining, and oxidative stress indices. Additionally, the ER stress and apoptosis indices were investigated by quantitative real-time PCR (qRT-PCR), Western blotting, and immunofluorescence (IF) on CP-induced toxicity in rat liver tissues and LO2 cells. In the model group, liver function indicators significantly elevated, liver lesions more pronounced, and the reactive oxygen species (ROS) level in the liver increased, the expression of ER stress markers, apoptosis factors, and indicators related to the protein kinase RNA-like ER kinase/activating transcription factor 4/C/EBP homologous protein (PERK/ATF4/CHOP) pathway significantly elevated. Treatment of the CP-induced toxicity in the rat model with GC significantly improved liver function, reduced liver lesions, decreased liver ROS. In addition, GC significantly inhibited the expression of ER stress markers, apoptosis factors, and indicators related to PERK/ATF4/CHOP pathway, demonstrating the anti-CP-induced hepatotoxicity effect of GC. In this study, we verified the protective effect of GC in CP-induced hepatotoxicity in rats and clarified its mechanisms related to ER stress and apoptosis.